Revealing genetic diversity, population structure, and selection signatures of the Pacific oyster in Dalian by whole-genome resequencing - Mao, Junxia; Tian, Ying; Liu, Qian; Li, Danyang; Ge, Xinfan; Wang, Xubo; Hao, Zhenlin (Frontiers in Ecology and Evolution, 2024)
The Pacific oyster (Crassostrea gigas), one of the major aquaculture shellfish worldwide, has strong environmental adaptability. However, genetic diversity and population structure of the Pacific oysters in Dalian Sea, the major natural and farming area of the species in China, has not been systematically investigated, especially at genome-wide level, limiting the conservation and management of the species. In this study, whole-genome resequencing of 105 individuals from seven Pacific oyster populations, including five wild (XST: Xingshutun, GLD: Guanglu island, SSD: Sanshan island, LHT: Laohutan, LS: Lvshun) and one cultured (CT) populations in Dalian and one wild population in Qingdao (QD) relatively distant from others, were first performed. A total of 2,363,318 single nucleotide polymorphisms (SNPs) were identified. Based on all these SNPs, similar but relatively low genetic diversity (0.2352~0.2527) was found in the seven populations. The principal component analysis (PCA), phylogenetic and population structure analysis consistently revealed weak differentiation among the seven populations. Though individuals from one population were not clearly separate from the other populations, they could be divided into two clusters with one including CT, SSD and LHT populations and another one including QD, GLD and XST populations, while the LS population were dispersedly distributed. Frequent migration events were detected among the studied populations by TreeMix, which probably led to a high genetic similarity of these populations. Rapid linkage disequilibrium (LD) decay was observed in the genome of the Pacific oyster. Investigation of genome-wide selection signatures of these populations identified many selected genes involved in the biological processes related to DNA metabolism and stability, shell formation, and environmental stress response, which may be critical for oysters to adapt to the stressful environments. This study laid theoretical basis for the subsequent germplasm conservation, management and genetic breeding of the indigenous Pacific oysters, and provided novel insights for the adaptive evolutionary mechanism of oysters.